(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE: To assess the short-term functional outcome after internal fixation of unstable ankle fractures. METHODOLOGY: This descriptive cross-sectional study was performed at the Department of Orthopaedics, Chandka Medical College (SMBBMU), Larkana, using non-probability consecutive sampling. Patients aged 18 to 65 years, either gender, presenting with unstable ankle fractures were enrolled. Postoperatively, patients were followed up in the outpatient department at one, three, and four months to assess the functional outcomes using the American Orthopedic Foot and Ankle Society (AOFAS) scoring system, which grades outcomes as Excellent (95–100), Good (75–94), Fair (51–74), and Poor (≤50). Data were analyzed using SPSS version 26, with a significance level of p ≤ 0.05. RESULTS: In the present investigation involving 179 subjects (mean age 39.77 years; 74.9% female, 25.1% male) diagnosed with unstable ankle fractures, the application of internal fixation resulted in exemplary outcomes in 35.8% of cases and satisfactory outcomes in 38.5%, as evaluated by AOFAS scoring metrics. The functional outcomes exhibited a statistically significant association with the Lauge Hansen fracture classification (p = 0.0001), with particularly favorable results noted within the supination-external rotation subgroup. Conversely, factors such as age (p = 0.318), gender (p = 0.593), and additional clinical parameters including smoking (p = 0.618), diabetes (p = 0.257), and type of fracture (p = 0.659) did not demonstrate a significant effect on the recovery process. CONCLUSION: This investigation elucidates that the internal fixation of unstable ankle fractures results in positive short-term functional outcomes, with a significant proportion of patients attaining excellent to good recovery as quantified by the AOFAS score. The outcomes were markedly affected by the fracture patterns categorized according to the Lauge Hansen classification system. These results substantiate internal fixation as a potent intervention for facilitating early postoperative recovery in cases of unstable ankle fractures.